Membangun Kesetaraan Gender dalam Perekrutan Kerja: Perlindungan Hukum bagi Pekerja Wanita terkait Cuti Melahirkan - Intan Nailul Muna; Alvieta Alice Reyhanif; Aulia Zaki; Neni Susilowati; Arum Nurul Layalia Mufaidah; Kuswan Hadji (Lembaga Pengembangan Kinerja Dosen, 2025)
Gender equality in the workforce is a fundamental issue closely linked to human rights and sustainable economic development. This study examines the paradox in the implementation of maternity leave rights as part of the legal protection for female workers—where a right intended to provide protection instead becomes a barrier during recruitment processes. The aim of this research is to analyze the relationship between the provisions on maternity leave rights and the principle of legal equality in the workplace, as well as to identify efforts that companies can undertake to protect female workers from discrimination and to promote gender equality. This study employs normative legal research methods with a qualitative approach by analyzing various national and international regulations related to the protection of female workers. Primary data were obtained through an in-depth review of Undang-Undang No. 13 Tahun 2003 tentang Ketenagakerjaan, Undang-Undang Dasar Negara Republik Indonesia Tahun 1945, and their implementing regulations, as well as international conventions such as CEDAW and ILO standards. The analysis was carried out using a deductive approach to identify the gap between legal norms and the reality of their implementation in practice.